Loseless Data Embedding Scheme for Medical Image Transmission in E-Diagnosis - Ann Ramola Jeyanthi, A.; Babu, B.; Vishnu Priya, T. S. (Asian Journal of Engineering and Applied Technology, 2012)
One of the major concerns throughout the world today is to make high quality health care available to all. Traditionally, part of the difficulty in achieving equitable access to health care has been that the provider and the recipient must be physically present in the same place. Recent advances in Information and Communication Technologies have increased the number of ways health care can be delivered to reduce these difficulties. Mobile phones are the most commonly used devices in today’s scenario. The expanding use of mobile phone, telecommunication companies added feature such as MMS (Multimedia Messaging Service) in order to attract more customers. The Multimedia Messaging Service (MMS) has became very popular for sending messages containing multimedia objects such as images, audio, or video clips among mobile users. Alongside, the need for the secure communication became more imperative. Steganography is the most reliable technique for hidden communication. Hiding information, especially in images has been an alternative solution for secret communication [2].